Legal Protection for Victims of Domestic Physical Violence from the Perspective of Justice Theory : Study of the Decision of the Sleman District Court No. 472/Pid.Sus/2016/Pn.Smn - Anglin Virgine Lumapow; Fransiska Alessandra Naomi; ensa, Ensalina Papilaya (International Journal of Law, Social Science, and Humanities, 2025)
Domestic physical violence is a violation of human rights that requires a fair and effective legal response to protect victims. This study aims to examine the practice of legal protection for victims of domestic physical violence which is interesting to question, especially from the perspective of justice, with a case study at Sleman District Court No.472/PID.SUS/2016/PN.SMN. By basing on the judiciary as a process of law enforcement and justice, qualitatively, the judge's consideration in the decision will be examined based on applicable law and Aristotle's theory of justice. The results of the study indicate that the one-year criminal sentence imposed on the perpetrator of physical violence in Case Number 472/PID.SUS/2016/PN.Smn, in terms of legal provisions, does not violate, because it is still within the maximum criminal sanction that can be imposed. However, in terms of justice, the sentence is too light and not proportional to the physical suffering experienced by the victim. The lenient punishment also does not provide a deterrent effect for perpetrators or potential perpetrators in the future. There needs to be a change in the attitude of the judge in favor of the victim, by giving a sentence that is comparable or more just from the victim's side, and provides a deterrent effect for perpetrators and potential perpetrators of violence. Keywords: Legal Protection, Criminal Act, Domestic Violence.